Square of an Enormously Large Number - Bhardwaj, Harsh (International Journal of Computer Sciences and Engineering, 2025)
In this world of extremely fast and effective manipulations and calculations, the requirements for the time taken by a computation needs to be nailed down to the extreme low as possible. The time required for calculations doesn't come up as an issue unless you type in a really huge number, like a number including 100-digits or so. When this kind of number is required to be processed upon, our computer systems take quite a while to process upon the operations being performed on the number. A process for quick and easily manipulated computations is required to be produced, in order to increase the productivity, convenience, ease of use and fairly deal with budgetary concerns. This document provides general practices, procedures and tools for creating a faster computation of square of extremely large numbers. It is aimed for engineers, Mathematical gurus, algorithm geeks, who are assumed to possess basic knowledge regarding what is meant by square of a number. It addresses basic knowledge about how to calculate the square using conventional means and how the improvement can be made to save time.